Planning Thoughts – The evolution of themes in Master Dissertations and Doctoral Theses in the field of specialisation in Spatial Planning, FEUP - Paulo Conceição; Isabel Breda Vázquez; Fernando Brandão Alves; Ana Rita Sousa; Jorge Afonso Rios; Daniel Sampaio Tavares (U.Porto Journal of Engineering, 2023)
The formal existence of a specialisation in spatial planning at FEUP dates back 50 years. The present paper aims to contribute to the analysis of this experience, and to some extent of its contributions, by tracing the evolution of the themes of MSc dissertations and PhD thesis. under the scope of the different spatial planning specialisation courses.